GOLD PAWN (AR-RAHN) IMPLEMENTATION IN INCREASING CUSTOMER LOYALTY (CASE STUDY PT. BPRS BHAKTI SUMEKAR PRAGAAN BRANCH) - Holilur Rahman; Luluk Mukarromah (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2020)
PT. BPRS Bhakti Sumekar plays an active role in the regional economic development of Sumenep Regency, this is proven by its existence PT. BPRS Bhakti Sumekar in every activity, either directly or indirectly related to the community as a form of corporate responsible for social welfare and the formation of agents in bill collection turns out to have a positive correlation in customer loyalty. This study aims to determine the implementation of gold pawn ar-rahn) in increasing customer loyalty at PT. BPRS Bhakti Sumekar Pragaan Branch, and is there any difference between practice and theory on gold pawn (ar-rahn) in increasing customer loyalty at PT. BPRS Bhakti Sumekar Pragaan Branch with relevant data sources and using observation techniques, interviews with the authorities, and documentation. In this study researchers used a qualitative method, namely the case study method by conducting direct field surveys. Data analysis uses data reduction, display data, and conclusion data. The results showed that the community was very enthusiastic about pawning their gold. However, since the corona'19 virus, gold pawning has decreased. Then the implementation of gold pawning at the BPRS Bhakti Sumekar Pragaan Branch was again due to the declining gold price, and increasingly fierce competition. so the Bank strives to increase it again so that customers are more tempted to pawn their gold than so the Bank makes efforts to increase it again so that customers are more tempted to pawn their gold than to sell.